Activity of compounds from Taxillus sutchuenensis as inhibitors of HCV NS3 serine protease. Issue 4 (16th February 2017) - Yang, Liyuan; Lin, Jun; Zhou, Bin; Liu, Yangang; Zhu, Baoquan
Abstract: This study aimed to isolate active compounds from traditional Chinese medicinal Taxillus sutchuenensis to inhibit hepatitis C virus (HCV) NS3 protease activity. Under the guidance of bioassay, 10 compounds were isolated from the EtOAc extract fraction, which were identified as inhibitors of HCV NS3 protease. IC50 values of these compounds were obtained, and a broad degree of anti-HCV activity was observed. The most active compounds were kaempferol-3, 7-bisrhamnoside (19.4 μM) and (3 S )-3-hydroxy-1, 7-bis(4-hydroxy-phenyl)-6 E -hepten-5-one (28.7 μM). In conclusion, flavonoids and diarylheptanoids were responsible for the anti-HCV constitution of Taxilli Herba . These inhibitors of HCV NS3 protease might serve as potential candidate of anti-HCV agents. Abstract :